First report of Colletotrichum nymphaeae causing leaf spot in Khaya spp. - Benso, L. A. [UNESP]; Pieroni, L. P. [UNESP]; Mira, Y. D. [UNESP]; Marques, A.; Ciriello, V.; Rossini, B. C. [UNESP]; Marino, C. L. [UNESP]; Furtado, E. L. [UNESP] (Springer Nature, 2023)
In a forest nursery located in Brazil, seedlings of Khaya spp. were observed showing leaf spot symptoms. From these symptoms, the phytopathogen Colletotrichum nymphaeae were isolated and characterized based on morphological, molecular and pathogenicity characteristics. To the best of our knowledge, this is the first report of C. nymphaeae infecting Khaya spp. in the world.
Keywords: African mahogany; Colletotrichum acutatum complex; Forest nursery; Glomerellaceae